Zwinne podejście do zarządzania procesem badawczo-rozwojowym - Bonecki, Mateusz (Wydawnictwo Naukowe UAM, 2014)
This paper analyzesthe evolution of research and development management methods. The so-called “agile approach” to project management is considered to have a great influence on knowledge-work organization and new product development methods. It is argued that agile organizations shape their R&D processes in accordance with the theory of complex adaptive systems and the principles of empirical process modeling in order to improve their responsiveness to market conditions or changing client requirements. Organizational agility is therefore conceived here as a function of interdisciplinary processing and the use of cross-domain knowledge about relevant factors that are present in a project’s external environment.
Keywords: research and development; agile; software development; scrum; B+R; badania i rozwój; zwinne metodyki